2017
DOI: 10.1016/j.cell.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Senescence in Health and Disease

Abstract: Many cellular stresses activate senescence, a persistent hyporeplicative state characterized in part by expression of the p16INK4a cell cycle inhibitor. Senescent cell production occurs throughout life and plays beneficial roles in a variety of physiological and pathological processes including embryogenesis, wound healing, host immunity and tumor suppression. Meanwhile, the steady accumulation of senescent cells with age also has adverse consequences. These non-proliferating cells occupy key cellular niches a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
1,080
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,324 publications
(1,187 citation statements)
references
References 105 publications
22
1,080
1
11
Order By: Relevance
“…Emphysema accompanies cellular senescence, and the incidence of this disease increases with age (Karrasch, Holz, & Jörres, 2008; Tsuji et al, 2006). Recent studies on the genetic and pharmacological ablation of senescent cells have demonstrated that these cells underlie several diseases (He & Sharpless, 2017). Our results also suggest that the elimination of p19 ARF ‐expressing cells in ARF‐DTR mice protects lung tissues against PPE‐induced emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…Emphysema accompanies cellular senescence, and the incidence of this disease increases with age (Karrasch, Holz, & Jörres, 2008; Tsuji et al, 2006). Recent studies on the genetic and pharmacological ablation of senescent cells have demonstrated that these cells underlie several diseases (He & Sharpless, 2017). Our results also suggest that the elimination of p19 ARF ‐expressing cells in ARF‐DTR mice protects lung tissues against PPE‐induced emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence plays an instrumental role in limiting the development of pathological states including cancer, but the accumulation of senescent cells with aging also contributes to age‐related tissue dysfunction (He & Sharpless, 2017). Cellular senescence is a complex phenotype characterized by two arms: a stress‐induced, durable cell cycle arrest and the production of a suite of pro‐inflammatory molecules known as the senescence‐associated secretory phenotype (SASP) (Childs, Durik, Baker & van Deursen, 2015; Coppe, Desprez, Krtolica & Campisi, 2010; Munoz‐Espin & Serrano, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Senescent cells are mainly characterized by a stable cell cycle arrest and the appearance of features such as senescence‐associated‐β‐galactosidase activity (SA‐β‐Gal) and senescence‐associated secretory phenotype (SASP; Kuilman, Michaloglou, Mooi, & Peeper, 2010). Senescence plays a key role in many pathophysiological contexts, such as embryonic development, wound healing, cancer, and aging (He, & Sharpless, 2017). Understanding how senescence is controlled at the molecular and cellular level is therefore crucial.…”
Section: Introductionmentioning
confidence: 99%